Effect on the inhibitory activity of potential microbes on the complexation of methyl anthranilate derived hydrazide with Cu, Ni and Zn(II) metal ions - Ur-Rehman, Saeed; Ul-Islam, Mazhar; Ikram, Muhammad; Rehman, Sadia; Shah, Syed Muhammad; Mahdi, Kamran; Ullah, Farhat (Eclética Química, 2014)
The present report is concerned with the synthesis and coordination compounds of 2-amino-(N-aminobezoyl) benzohydrazide[ABH]. The ligand was charcterized by proton NMR, mass spectrometry, elemental and infrared studies. The ligand has got –NH2 moeity which is capable of chelation. Therefore complexes of Ni, Cu, and Zn were prepared. These complexes were characterized by elemental, infrared, thermal, conductance, and magnetic susceptibility studies. Infrared spectra shows that the ligand form complexes through –NH2 moeity, while the elemental studies suggest M(ABH)X2 composition of the coordination compounds. Knowing about the importance of -N-N- linkage in the biologically active compounds, the synthesized complexes were studied for their biological activities against Gram Negative bacteria which include E. coli, Salmonella typhi, Enterobacter aerogenes, Proteus vulgaris and Pseudomonas aeruginosa, selected Gram Positive bacterial strain is Staph aureus and Fungus like Candida albican. These activities show that the hydrazide containing metal complexes become more potentially resistive to the microbial activities as compared to the sole ligand.